The influence of patients infected with H1N1 influenza A virus on acute kidney injury - LI Rui Ying-xin; LI Ying-xin (Linchuang shenzangbing zazhi)
Objective To retrospectively review the clinical characteristics of severe and critically ill patients infected with 2009 pandemic influenza A(H1N1) virus,and analyze the factors associated with acute kidney injury(AKI) in HlNl-infected patients.Methods There were 145 patients from Oct 2009 to May 2013 meet the inclusion criteria of Ministry of Health involved.According to the guideline published by the Ministry of Health,all of the patients were classified into two groups:severe group and critically ill group.The data of demographics,baseline characteristics,clinical course,length of hospital stay,laboratory values,APACHE Ⅱ score,mortality,the incidence of AKI,and other supplemental data were collected.All the patients have accepted synthesized therapy,including mechanical ventilation and drug intervention.Blood purification was implemented if the patients met the indication of dialysis.Results The severe H1N1 group was composed of 97 cases,and critically ill group 48 cases.The levels of LDH,CK,APACHE Ⅱ score were higher respectively in critically ill group than in severe group(P<0.01).The levels of oxygenation index,platelet count,lymphocyte count were also increased obviously in critically ill group as compared with those in severe group(P<0.01).The incidence of AKI in critically ill group was 16.7%,which was higher than 3.1%in severe group.A significant difference in levels of BUN,SCr and Cys C was found between severe and critically ill groups.Most of the data in critical ill group were higher on days 1,3,7,14 of hospital admission(P<0.01).Conclusions Much higher incidence of AKI was observed in critically ill group.AKI could lengthen the hospital stay and increase the mortality.